Exploring the Experience of Novice ELT Lecturers to build their Professional Identity Based on Tri Dharma Perguruan Tinggi - Zizanatin Nur Lailia; Ada Marie Mascarinas (Universitas PGRI Adi Buana Surabaya, 2023)
Tri Dharma Perguruan Tinggi comprises Education, Teaching, Research, and Community Service. Every institution lecturer must carry out the Tri Dharma Perguruan Tinggi, especially for novice ELT lecturers who are incoming in new cultural education in English Language and don’t have lecturer certification. This research aims to explore the novice ELT lecturers’ experience in fulfilling the three pillars of Tri Dharma Perguruan Tinggi to build their professional identity. Accordingly, the objectives were to find out how the experience of novice ELT lecturers builds their professional identity based on the Tri Dharma Perguruan Tinggi. Qualitative research in the form of a narrative is used as a research approach. The data were analyzed using thematic analysis. Data were collected through an interview with the study participants: the four novices ELT lecturers in English Education Department at PGRI Adi Buana University Surabaya. The findings show that there is a learning system and teaching material from pillar one. In pillar two, there is research and publication, and pillar three finds their experience in a group of community service.